2010
DOI: 10.1128/jcm.01526-09
|View full text |Cite
|
Sign up to set email alerts
|

Sputum Mycobacterium tuberculosis mRNA as a Marker of Bacteriologic Clearance in Response to Antituberculosis Therapy

Abstract: mRNA is a marker of cell viability. Quantifying Mycobacterium tuberculosis mRNA in sputum is a promising tool for monitoring response to antituberculosis therapy and evaluating the efficacy of individual drugs. mRNA levels were measured in sputum specimens from patients with tuberculosis (TB) receiving monotherapy in an early bactericidal activity study of fluoroquinolones and in those receiving a standard rifampin-based regimen in an interleukin-2 (IL-2) trial. In the early bactericidal activity study, sputum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…Previous reports have suggested that abundant mRNA species such as fbpB-85B and icl may be useful for the detection of live bacilli (5,9,10,15). While the clearance of the icl gene showed promise as a biomarker for a fall in CFU at 7 days, it did not match liquid culture sensitivity at day 56.…”
mentioning
confidence: 74%
“…Previous reports have suggested that abundant mRNA species such as fbpB-85B and icl may be useful for the detection of live bacilli (5,9,10,15). While the clearance of the icl gene showed promise as a biomarker for a fall in CFU at 7 days, it did not match liquid culture sensitivity at day 56.…”
mentioning
confidence: 74%
“…These include the PCR [12,42], antigen 85 induction [69,70], whole blood bactericidal assay [71,72], the Early bactericidal activity of antituberculosis drugs Review www.expert-reviews.com measurement of mRNA [73,74], molecular bacterial load assay [75] and most recently the use of GeneXpert MTB/RIF to quantitate mycobacteria in sputum [76,77]. Each of these techniques could potentially either add value to the current determination of the fall in sputum CFU counts or replace it.…”
Section: Alternative Means Of Determining Ebamentioning
confidence: 98%
“…This innovative concept must be confirmed in a future study. Recently, RNA detection with RT-PCR has also been used to determine bacterial viability in other infectious diseases (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%